Does Health Reform Reduce Inequalities?: Primary Healthcare Utilization of Young Children in Turkey - Caner, Asena; Karaoğlan, Deniz; Yaşar, Gülbiye Yenimahalleli (Taylor and Francis, 2025)
We investigate whether the family medicine system introduced as part of the Turkish Health Transformation Programme immediately equalized utilization of health services between young children from low-and high-resource households. Using difference-in-differences analysis, we compare the change in service utilization over time between the two groups of children, using official nationally representative microdata from the Health Research Surveys in 2008, 2010, and 2012. Overall, the effect of the reform depends on the measure of utilization. Considering ‘being taken to a health institution’ as the measure, we find no evidence for a positive differential effect on children from low-resource households. On the other hand, considering ‘being taken to a health institution when not sick’, the reform benefited children from lower-resource households more than it benefited better-off children. The evidence for having new-born screening is weak. Regarding the utilization of family health centres, we find no evidence for a positive differential effect for lower-resource households. © 2025 Elsevier B.V., All rights reserved.